2019
DOI: 10.29271/jcpsp.2019.10.919
|View full text |Cite
|
Sign up to set email alerts
|

Association Between Neutrophil-to-Lymphocyte Ratio and Mortality in Neurological Intensive Care Unit Patients

Abstract: Objective: To investigate the effect of neutrophil-lymphocyte ratio (NLR) on survival and mortality in patients who were interned in the Neurology Intensive Care Unit (NICU).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 18 publications
0
2
0
Order By: Relevance
“…For example, it has been reported that NLR being > 10.45 on day 2 and > 7.91 on day 5 is an independent predictor for in-hospital mortality 19 . Approximately 5 to 15 different cut-off values were obtained for NLR in the diagnosis of patients with sepsis, presence of bacteremia and mortality 9,10,17,[20][21][22][23] . In our results, the cut-off value for NLR in predicting the mortality of sepsis was 9.2.…”
Section: Discussionmentioning
confidence: 99%
“…For example, it has been reported that NLR being > 10.45 on day 2 and > 7.91 on day 5 is an independent predictor for in-hospital mortality 19 . Approximately 5 to 15 different cut-off values were obtained for NLR in the diagnosis of patients with sepsis, presence of bacteremia and mortality 9,10,17,[20][21][22][23] . In our results, the cut-off value for NLR in predicting the mortality of sepsis was 9.2.…”
Section: Discussionmentioning
confidence: 99%
“…The neutrophil/lymphocyte ratio (NLR) is a strong biomarker, indicating acute and chronic inflammatory status, is reliable, cost-effective, and easily applicable, and is considered as a stronger inflammatory marker than the individual assessment of the neutrophil count or lymphocyte count [7][8][9][10]. The platelet/lymphocyte ratio (PLR), monocyte/lymphocyte ratio (MLR), mean platelet volume/lymphocyte ratio (MPVLR), mean platelet volume/platelet ratio (MPVPR) are the parameters that are easily calculated from the complete blood count.…”
mentioning
confidence: 99%